Efektivitas Pelayanan One Day One Service Penerbitan Akta Kelahiran di Rumah Sakit Umum Daerah Syarifa Ambami Rato Ebu Bangkalan - Izza A'ilah, Raffiula; Weni Rosdiana (Jurnal Inovasi Administrasi Negara Terapan, 2023)
A birth certificate is an important document that everyone must have. The implementation of issuing birth certificates was initiated by RSUD Syarifa Ambami Rato Ebu Bangkalan, in collaboration with Dispendukcapil Bangkalan District to provide services at the hospital. This service has been running for a long time since 2017, in its implementation there are problems that affect the effectiveness of the service. This is what makes researchers interested in discussing the effectiveness of the one day one service birth certificates issuance at the Syarifa Ambami Rato Ebu Bangkalan Regional Hospital. This research use descriptive qualitative approach. Data sources used include primary data and secondary data, data collection techniques include observation, interviews, documentation and literature study. Data analysis was carried out by collecting data, reducing data, presenting data and concluding/verifying. The results of the research are based on the 5 indicators of effectiveness presented by Sutrisno, the one day one service for issuing birth certificates can only fullfil 1 indicator while the other 4 indicators are not, the 4 indicators are: (1) Program understanding, hospital officials do not understand socialization indirectly to the community, which makes the community confused in managing the service, while the Bangkalan Regency Population and Civil Registration Department officials do not understand that this service must be carried out within 1 day, which makes the service late. (2) On time, this is because there is only 1 person from the Bangkalan Regency Population and Civil Registration Department who handles requests from hospitals and they still have to provide population document services in villages in Bangkalan. Apart from that, it is also because people do not understand how to handle the service. (3) Achievement of Goal, the goal was not achieved because there was still a service time problem which meant that this service could not be carried out within 1 day. (4) Real Changes, do not have a significant change impact because there are still problems in service implementation. The one day one service for issuing birth certificates at the Syarifa Ambami Rato Ebu Bangkalan Regional General Hospital is still far from effective because there are still many problems that need to be resolved.   Keywords: Efektivness, One Day One Service, Birth Certificate